Монгол хэлний хэм хэмжээ зөрчигдөх үзэгдлийг тархины цахилгаан долгионы тэмдэглэх аргаар туршин судлах нь: Experimenting phenomenon of Mongolian language norm violation by measuring erps - Зулаа (Mongolian Studies, 2023)
The present study aims to experiment how brain of native speakers response to the violation of Mongolian orthographic and orthoepic norm measuring their ERPs with special means of electroencephalography (EEG)